3.B. Workshop: Quality of COVID-19 science: meta-research and the ethical implications for public health. (25th October 2022) - ,; ,
Abstract:  : Since the beginning of the COVID-19 pandemic, scientific researchers have had to balance the need to disseminate information rapidly while still maintaining high-quality standards of research design and reporting. Early meta-research efforts comparing the methodological quality of COVID-19 research with pre-pandemic medical research found a higher prevalence of observational studies with a shorter time from submission to acceptance, lower methodological quality scores, higher risk of bias, and lower number of participants. This workshop is intended to showcase some public health relevant meta-research that has assessed COVID-19 study quality during later phases of the COVID-19 pandemic, analysed transparency and integrity indicators, and revisited earlier studies in the light of stronger evidence. After three more technical presentations that will examine the role of meta-research in addressing some of the COVID-19 pandemic research challenges, an ethical overview of the concept of "the science" as an idea used in public decision-making and policy will be given. Key messages:  Meta-research role of scrutinizing evidence as it is produced is even more important when scientific information is diffused at an expedited rate.  Ethical questions might be as relevant as epidemiological ones when science is not able to be all that leads decision-making.